Complete genome sequences of Geobacillus sp. Y412MC52, a xylan-degrading strain isolated from obsidian hot spring in Yellowstone National Park. Issue 1 (December 2015) - Brumm, Phillip; Land, Miriam; Hauser, Loren; Jeffries, Cynthia; Chang, Yun-Juan; Mead, David
Abstract Geobacillus sp. Y412MC52 was isolated from Obsidian Hot Spring, Yellowstone National Park, Montana, USA under permit from the National Park Service. The genome was sequenced, assembled, and annotated by the DOE Joint Genome Institute and deposited at the NCBI in December 2011 (CP002835). Based on 16S rRNA genes and average nucleotide identity, Geobacillus sp. Y412MC52 and the relatedGeobacillus sp. Y412MC61 appear to be members of a new species ofGeobacillus . The genome ofGeobacillus sp. Y412MC52 consists of one circular chromosome of 3, 628, 883 bp, an average G + C content of 52 % and one circular plasmid of 45, 057 bp and an average G + C content of 45 %. Y412MC52 possesses arabinan, arabinoglucuronoxylan, and aromatic acid degradation clusters for degradation of hemicellulose from biomass. Transport and utilization clusters are also present for other carbohydrates including starch, cellobiose, and α- and β-galactooligosaccharides.